Green synthesis of stable and biocompatible fluorescent carbon dots from peanut shells for multicolor living cell imaging. (21st December 2015) - Xue, Mingyue; Zhan, Zhihua; Zou, Mengbing; Zhang, Liangliang; Zhao, Shulin
Abstract : Fluorescent carbon dots derived from peanut shells were prepared via a pyrolysis approach and used for living cell imaging. Abstract : A green approach for the synthesis of fluorescent carbon dots (C-dots) with a quantum yield of about 9.91% has been developed using peanut shells as a precursor. The C-dots were prepared via a simple pyrolysis of peanut shells. The obtained C-dots exhibit an excitation-dependent manner, excellent stability, high photostability, and good tolerance for pH, ionic strength and photobleaching. The cytotoxicity of the C-dots was also evaluated using HepG2 cells, and the cell viabilities were estimated to be greater than 90% upon addition of the C-dots over a wide concentration range from 0 to 1.2 mg mL −1 . Based on the abovementioned merits, we also applied the prepared C-dots as an effective fluorescent probe for multicolor living cell imaging.